Metode Shift Share pada Produk Domestik Regional Bruto di Kabupaten Bulungan - Nur, Adi Aspian (STIE Jambatan Bulan, 2021)
The purpose of this study was to determine the leading and non-superior sectors through the GRDP data of Bulungan Regency and GRDP of North Kalimantan Province. The data in the study is secondary data originating from the Central Statistics Agency (BPS) in the form of GRDP data at the base prices that apply according to business fields in 2014-2018. With quantitative research methods and Shift Share analysis, it can be seen which sectors are superior and not superior in the region. Based on the Shift Share analysis, there are 4 superior economic sectors, namely: (1) Construction; (2) Wholesale and Retail Trade; Car and Motorcycle Repair; (3) Transportation and Warehousing; and (4) Provision of accommodation and food and drink. The others 13 sectors did not potencial.